1983
DOI: 10.1016/0014-5793(83)80787-x
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni: antigenic community between schistosomula surface and adult worm incubation products as a support for concomitant immunity

Abstract: The use of protective monoclonal antibodies has enabled us to demonstrate antigenic community between a 38‐kDa schistosomula surface molecule and a 115‐kDa component derived from adult worms. Injection of adult worms in rats also led to the production of antibodies specific for the 38‐kDa antigen, suggesting that the 115‐kDa adult worm molecule could act as an inducer of the protective immune response raised against young invading parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…These findings exclude the possibility that SRP-A IgE antigens could be a molecular support for the concept of concomi tant immunity, whereas this was previously described with the target antigens of monoclonal IgG2a, which displayed antigenic identity between a 115-kDa adult-worm molecule and a 38-kDa schistosomulum sur face molecule [29]. It is worth to notice that these re sults were restricted to the anti-SRP-A IgE response, since SRP-A without adjuvant were able to induce a significant cytotoxic lgG2a response [30], In our preparative experiments, the cytotoxic ac tivity of serum anti-fraction 8 (26 kDa) 10 (22 kDa) was each weaker than that of the anti-SRP-A or in fected rat sera.…”
Section: Discussioncontrasting
confidence: 40%
“…These findings exclude the possibility that SRP-A IgE antigens could be a molecular support for the concept of concomi tant immunity, whereas this was previously described with the target antigens of monoclonal IgG2a, which displayed antigenic identity between a 115-kDa adult-worm molecule and a 38-kDa schistosomulum sur face molecule [29]. It is worth to notice that these re sults were restricted to the anti-SRP-A IgE response, since SRP-A without adjuvant were able to induce a significant cytotoxic lgG2a response [30], In our preparative experiments, the cytotoxic ac tivity of serum anti-fraction 8 (26 kDa) 10 (22 kDa) was each weaker than that of the anti-SRP-A or in fected rat sera.…”
Section: Discussioncontrasting
confidence: 40%
“…Moreover, Bickle, Andrews & Taylor (1986) have described a monoclonal antibody which recognises a M,32000 surface antigen and binds to the schistosomulum for up to 72 h post-transformation, which also weakly recognises the surface of lung schistosomula. Studies by other workers have also shown that a periodate sensitive Mr38000 antigen is present on the surface of newly transformed schistosomula but that it disappears relatively rapidly from the parasite, and is totally absent from the surface of lung stage schistosomula (Dissous, Grzych & Capron 1982, Dissous & Capron 1983, Simpson et al 1984. Thus the temporal separation of eosinophil-dependent killing of schistosomula mediated by anti-SAg/CHO and anti-SAg/PEP antibodies may be accounted for by a modulation on the larval surface of the antigens Mr32000 and 38000.…”
Section: Discussionmentioning
confidence: 95%
“…The regime of periodate treatment as used here was found to be without effect on the ability of treated BSA to react in immunodiffusion against anti-BSA (Dunne & Bickle 1987) and although protein epitopes more sensitive than those of BSA may be involved (Beeley 1985) the periodate sensitivity suggests that the target epitopes of the MoAbs involve carbohydrate. Dissous & Capron (1983) reported that the target for their anti-M, 38 000 MoAb was periodate sensitive and that its presence in a number of apparently different sized molecular structures in the different developmental stages (Dissous, Grzych & Capron 1986) could be explained if it were found on carbohydrate chains linked to different protein structures. Such an explanation would be consistent with the present results, and the demonstration of three differing patterns of reactivity in our immunodiffusion analysis suggests that the carbohydrate chains on the schistosomular surface contain at least three differing epitopes.…”
Section: Discussionmentioning
confidence: 99%